Effect of sporulation conditions following solid-state cultivation on the resistance of Geobacillus stearothermophilus spores for use as bioindicators testing inactivation by H2O2. (November 2021) - Stier, Philipp; Maul, Sabrina; Kulozik, Ulrich
Abstract: Geobacillus stearothermophilus spores play an essential role in the pharmaceutical and food industries as bioindicators (BI) to evaluate inactivation effects of hydrogen peroxide in processing and packaging lines' sterilization. Unstandardized, inconsistent BI production, as is the case for currently available commercial BI, can lead to variable resistances and incorrect test results. The solution to this problem could be the standardization of BI spore production. This study assessed the effects of sporulation temperature and pH on spore resistance in the production of G. stearothermophilus ATCC 7953 spores on solid-state agar. For this purpose, spores were produced under different sporulation conditions (51–63 °C, pH 6–8), and their resistance was determined by the D-value in 35% liquid hydrogen peroxide at 25 °C. Based on these data, a mathematical equation describing the resistance as a function of the sporulation conditions was derived. The analysis showed a quadratic effect of the sporulation temperature and a linear effect of the examined domain's pH on the resistance, without interactions between these factors. We observed the highest D25C, 35%H2O2 -value of 309 s at sporulation conditions of 57 °C and pH 6.0. Highlights: Sporulation temperature and pH highly impact spore resistance against H2 O2 . The sporulation temperature (51–63 °C) has a quadratic effect on the resistance. The pH of the sporulation medium (pH 6–8) has a linear effect on the resistance. The pH and temperature do not interact in their influence on the resistance.